Integration of Transcriptomics and Metabolomics Reveals the Antitumor Mechanism Underlying Shikonin in Colon Cancer - Chen, Yang; Gao, Yun; Yi, Xiaojiao; Zhang, Jinghui; Chen, Zhongjian; Wu, Yongjiang (Frontiers in Pharmacology, 2020)
Objectives: Colorectal cancer (CRC) is a common malignancy occurring in the digestive system, which is the third common cause for cancer mortality in developed countries. Shikonin, a naphthoquinone compound extracted from the root of Lithospermum erythrorhizon, is extensively reported to exert antitumor activity against various types of cancer. However, the systematic effect of Shikonin in colon cancer remains poorly understood. Methods: In the present study, we evaluated the antitumor activity of Shikonin in human colon cancer cells and the therapeutic effect on a xenograft mouse model. Transcriptomics and metabolomics were further integrated to provide a systematic perspective of shikonin-induced antitumor mechanism. Results: The results demonstrated that Shikonin had a remarkable antitumor potency both in vitro and in vivo. Moreover, metabolic pathways, including purine metabolism, amino acid metabolism and glycerophospholipid metabolism were perturbed and subsequently led to cell cycle arrest in G2/M phase. In particular, purine metabolism may account for the main antitumor mechanism of Shikonin. Conclusion: Shikonin has a cytotoxic effect against colon cancer both in vitro and in vivo, the disturbance of purine metabolism may account for the major mechanism resulting from Shikonin antitumor activity.